2020
DOI: 10.1155/2020/1380504
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics Analysis of Genes and Mechanisms in Postherpetic Neuralgia

Abstract: Objective. Elderly patients are prone to postherpetic neuralgia (PHN), which may cause anxiety, depression, and sleep disorders and reduce quality of life. As a result, the life quality of patients was seriously reduced. However, the pathogenesis of PHN has not been fully elucidated, and current treatments remain inadequate. Therefore, it is important to explore the molecular mechanism of PHN. Methods. We analyzed the GSE64345 dataset, which includes gene expression from the ipsilateral dorsal root ganglia (DR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…The results of GO enrichment showed that DEGs from the PHN rat model were mainly concentrated in the biological process of "cellular calcium ion homeostasis, " "positive regulation of cytosolic calcium ion concentration, " cell component of "voltage gated calcium channel complex, " and molecular function of "calcium ion binding" (Supplementary Figure 1). Consistent with previous reports, KEGG signaling pathway analysis showed that DEGs in DRG of the PHN rat model were mainly enriched in "calcium signaling pathway, " "neuroactive ligand-receptor interaction, " and "serotonergic synapse" (Supplementary Figure 2; Qiu et al, 2020). Encouragingly, our results further revealed that the GO enrichment and KEGG signaling pathway analysis of 52 identical DEGs (Figure 6) obtained from the VZV-infected SH-SY5Y cells and the VZV-induced PHN rat DRG all showed calcium signaling-related items (Table 2).…”
Section: Discussionsupporting
confidence: 90%
“…The results of GO enrichment showed that DEGs from the PHN rat model were mainly concentrated in the biological process of "cellular calcium ion homeostasis, " "positive regulation of cytosolic calcium ion concentration, " cell component of "voltage gated calcium channel complex, " and molecular function of "calcium ion binding" (Supplementary Figure 1). Consistent with previous reports, KEGG signaling pathway analysis showed that DEGs in DRG of the PHN rat model were mainly enriched in "calcium signaling pathway, " "neuroactive ligand-receptor interaction, " and "serotonergic synapse" (Supplementary Figure 2; Qiu et al, 2020). Encouragingly, our results further revealed that the GO enrichment and KEGG signaling pathway analysis of 52 identical DEGs (Figure 6) obtained from the VZV-infected SH-SY5Y cells and the VZV-induced PHN rat DRG all showed calcium signaling-related items (Table 2).…”
Section: Discussionsupporting
confidence: 90%
“…Acute herpes zoster virus infection can cause irreversible damage to the body's nervous system, including the central and peripheral nerves (19). This view has been recognized and confirmed by many studies, but how nerve damage occurs is not clear (20,21). Moreover, current studies have not yet determined the mechanism of acute pain and persistent pain caused by herpes zoster virus infection (22).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, bioinformatic analysis has been generally performed in the identification of biomarkers, which provides insight into the molecular mechanism of disease progression (5)(6)(7)(8)(9). Microarray technology can be used for a wide range of bioinformatic analysis and the development of new computational techniques remains an active area of bioinformatics research that will continue to expand over the coming years (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%